Lidocaine-Loaded Solid Lipid Microparticles (SLMPs) Produced from Gas-Saturated Solutions for Wound Applications - Clara López-Iglesias; Cristina Quílez; Joana Barros; Diego Velasco; Carmen Alvarez-Lorenzo; José L. Jorcano; Fernando J. Monteiro; Carlos A. García-González (MDPI AG, 2020)
The delivery of bioactive agents using active wound dressings for the management of pain and infections offers improved performances in the treatment of wound complications. In this work, solid lipid microparticles (SLMPs) loaded with lidocaine hydrochloride (LID) were processed and the formulation was evaluated regarding its ability to deliver the drug at the wound site and through the skin barrier. The SLMPs of glyceryl monostearate (GMS) were prepared with different LID contents (0, 1, 2, 4, and 10 wt.%) using the solvent-free and one-step PGSS (Particles from Gas-Saturated Solutions) technique. PGSS exploits the use of supercritical CO2 (scCO2) as a plasticizer for lipids and as pressurizing agent for the atomization of particles. The SLMPs were characterized in terms of shape, size, and morphology (SEM), physicochemical properties (ATR-IR, XRD), and drug content and release behavior. An in vitro test for the evaluation of the influence of the wound environment on the LID release rate from SLMPs was studied using different bioengineered human skin substitutes obtained by 3D-bioprinting. Finally, the antimicrobial activity of the SLMPs was evaluated against three relevant bacteria in wound infections (Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa). SLMPs processed with 10 wt.% of LID showed a remarkable performance to provide effective doses for pain relief and preventive infection effects.